PENGELOLAAN KEUANGAN DI DESA PULAU LAWAS KECAMATAN BANGKINANG SEBERANG KABUPATEN KAMPAR TAHUN 2012 - Firmansyah "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
village finance availability is one of the principal component in villagedevelopment execution. this matter is need ability from village government tomanaged village finance effectively and efficient to subsidize villagedevelopment execution. Village finance management by island villagegovernment Lawas district Bangkinang across used for financing villagegovernment and village development financing. aim from this watchfulnessdetects village finance management at island village Lawas district Bangkinangacross year 2012 and factors that causes less village finance management themaximal at island village Lawas district Bangkinang across year 2012.this watchfulness location at island village Lawas district Bangkinang acrosscamphor regency Provinsi Riau. this watchfulness kind descriptive watchfulnesswith watchfulness method that is used watchfulness method that usequantitative method with makes tabulation gathered from watchfulnessrespondent.this watchfulness result at island village Lawas district Bangkinang across year2012,unfavorable. this matter visible from respondent answer recapitulationtable, knowable average respondent answer that give good answer numbers 3person (27,78 %, unfavorable answers number 7 person (56,94 %) and notgood only number 2 person (100,00 %) from watchfulness respondent answeraverage totals. furthermore factors that causes less finance management themaximal at island village Lawas district Bangkinang across year 2012, causedby ability SDM limited village, supervision less walk from bpd, societyparticipation under communication with supporter facilities in village financemanagement less available.keyword: effectiveness, village finance, and management efficiency